A Comparison of Springtime Pollen and Nectar Foraging in Honey Bees Kept in Urban and Agricultural Environments - McMinn-Sauder, Harper; Lin, Chia-Hua; Eaton, Tyler; Johnson, Reed (Frontiers in Sustainable Food Systems, 2022)
Spring is an essential time for honey bee foraging in temperate climates. This is a period of increased brood rearing supporting colony growth and demands access to high-quality pollen and nectar resources. With the expansion of urban and agricultural landscapes, the availability of pollen and nectar producing flowers is declining in many areas. We aim to determine how patterns of spring pollen and nectar foraging differ between colonies surrounded by varying degrees of urban and agricultural intensity, as well as to assess the potential for nectar sampling to serve as a proxy for pollen collection. Thirteen apiaries in Central Ohio, along a gradient of urban and agricultural intensity, were monitored in spring of 2019 through the periodic collection of pollen and nectar samples and continuous colony weight monitoring. We found that spring honey bees in urban and agricultural areas gain comparable amounts of weight and use similar spring resources. Foraging was heavily focused on flowering trees and shrubs including Malus (apple), Salix (willow), and Prunus (cherry), until the beginning of clover bloom (Trifolium spp.). We also identified differences in pollen and nectar foraging within colonies, with nectar containing fewer species collected more evenly than matched pollen samples. These results demonstrate that honey bees in both agricultural and urban environments exhibit similar foraging patterns during the spring, and that plant species important for nectar collection are substantially different from plants important for pollen foraging.